Long-Term Fire Regime Modifies Carbon and Nutrient Dynamics in Decomposing Eucalyptus pilularis Leaf Litter - Butler, Orpheus M.; Lewis, Tom; Rezaei Rashti, Mehran; Chen, Chengrong (Frontiers in Forests and Global Change, 2020)
The changes in fire regimes expected under climate change are likely to disrupt the biogeochemical cycling of carbon (C) and nutrients in forest ecosystems. Plant litter decomposition is a critical step in the terrestrial biogeochemical cycle, and is an important determinant of fire fuel load and forest C balance. We conducted a 277-day leaf litter decomposition experiment in an Australian eucalypt forest to test whether three contrasting, long-term fire regimes (no burning, 4-yearly burning, and 2-yearly burning) were associated with different C and nutrient dynamics during litter decomposition. Fire regime had strong effects on many litter properties, including overall rates of decomposition and C loss, which were greatest in the NB treatment, suggesting that fire regime can modify the rate at which C is returned from litter to soil or the atmosphere. This has potentially important implications for soil C storage and atmospheric CO2 concentrations under a changing climate. High-frequency fire was associated with litter nutrient depleting and high microbial nutrient demand, but did not affect nutrient loss rates from decomposing litter, suggesting conservative use and retention of nutrients by the litter microbial biomass. These effects differed qualitatively between 2-yearly and 4-yearly burning regimes, and they show how decadal-scale increases in fire frequency might contribute to soil nutrient depletion by disrupting decomposition. Many effects of fire regime on litter properties throughout decomposition were sensitive to litter bag retrieval date, suggesting that seasonal factors moderate the effects of fire regime, and that the role of fire regime-altered litter chemistry in shaping decomposition may be secondary to that of fire regime-altered environmental variables. Together, our findings highlight the potential consequences of long-term increases in prescribed fire frequency for litter decomposition and the storage and cycling of C and nutrients in eucalypt forests, and reveal the specific importance of average burn frequency in this context.